MODEL DISCOVERY LEARNING BERBANTUAN MEDIA ADOBE FLASH CS 6 PADA MATERI HUKUM NEWTON - Sipahutar, Melva; Dani, Rahma; Hendri, Menza (EduFisika: Jurnal Pendidikan Fisika, 2018)
This study aims to improve learning outcomes on the cognitive aspects of students of class X IPA 4 SMA Negeri 10 Kota Jambi on Newton's Law material by using Adobe Flash Cs 6. Learning Media This research is a classroom action research consisting of three cycles. Each cycle includes planning, execution, observation, and reflection. Qualitative data taking with observation of student activity using observation sheet while quantitative data collection that is to know improvement of student learning result by using test (Formative replication) at each end of cycle. In the first cycle the expected learning results are not in accordance with the KKM determined by the school that is 72, on the second cycle there is an increase in learning outcomes but have not reached the KKM that has been determined after the improvement at the time of teaching on cycle III learning outcomes achieved by students have been appropriate with KKM. Based on these results can be concluded that the use of Adobe Flash Cs6 learning media can improve student cognitive learning outcomes.